Taking education to the next level: What can be learned from benchmarking education across economies? - Natalie Chun; Elisabetta Gentile (Asian Development Bank (ADB), 2020)
Benchmarking is intended to help gauge where economies rank relative to others. However, historically educational benchmarking has often elected to use indicators based on their ease of availability, rather than a clear and defined link between inputs and learning outcomes. In this paper, we present a new approach to benchmarking. Developing and undertaking a systematic documentation of 171 indicators on basic and secondary educational inputs covering 69 economies, we analyze indicators that are significantly correlated with higher levels of learning outcomes. We find evidence that only six key inputs are associated with higher learning outcomes: gross enrollment in secondary school; targeted public information that reveals student gaps; strategic budgeting that provides programs for at-risk students; teacher quality that ensures wages are high and incentives are aligned with learning outcomes; information collection that enables timely, data-driven decision-making; and curriculum content that is matched to student skills. This work is seen as an important step for future benchmarking exercises in prioritizing investments in educational inputs that deliver improved educational outcomes independent of the economy and cultural context.
Keywords: H52; I22; I23; I25; 330; basic education; education benchmarking; higher education; skill outcomes; TVET